(untitled) (Clinics, 2021)
OBJECTIVES: Malignant melanoma (MM) is an invasive tumor that poses a threat to patient health. Circular RNAs (circRNAs) are important regulators of MM carcinogenesis. In this study, we investigated the expression characteristics and biological functions of, and mechanism underlying, circ_0119872 expression in MM. METHODS: Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was employed to examine the circ_0119872, microRNA (miR)-582-3p, and E2F transcription factor 3 (E2F3) mRNA expression levels in MM tissues and cell lines. Western blotting was performed to quantify E2F3 protein expression. MM cells with circ_0119872 knockdown were established, and cell counting kit 8 (CCK-8) and transwell assays were utilized to examine the function of circ_0119872 and its effects on the malignant characteristics of MM cells. The MiRDB and TargetScan databases were used to predict the target genes of miR-582-3p. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis was used to explore the biological functions of the target genes of miR582-3p. Additionally, a dual-luciferase reporter gene experiment was performed to verify the targeting relationship between circ_0119872 and miR-582-3p as well as that between miR-582-3p and E2F3. RESULTS: Circ_0119872 was remarkably upregulated in MM tissues and cell lines. Circ_0119872 knockdown suppressed the cell proliferation and metastasis In addition, miR-582-3p was identified as a downstream target of circ_0119872. The target genes of miR-193a-3p are involved in melanogenesis and cancer-related signaling pathways. Mechanistically, circ_0119872 facilitated MM progression by adsorbing miR-582-3p and upregulating E2F3 expression. CONCLUSION: Circ_0119872 is an oncogenic circRNA that participates in the promotion of MM progression by regulating the miR-582-3p/E2F3 axis.